Вы находитесь на странице: 1из 27

Page 5-1

Section 5: Sequences And Series

5.1

SEQUENCES

5.1.1 Basic Definitions Concerning Sequences

Definition 1:

A sequence is a function whose domain is the set of positive integers.

Notation for Sequences:

Let u(n), with n

When we use this notation, u n will be called the n th term of the sequence.

N, be a sequence. We will denote this sequence by {u n } or {u 1 , u 2 ,

,

u n ,

.}.

Definition 2:

Let A R. A is said to be bounded above if there exists α R such that a α for each

a A. Further, such an α is said to be an upper bound for A.

Similarly, A is said to be bounded below if and only if there exists β R such that

β a for each a A. Further, such a β is said to be a lower bound for A.

Finally, A is said to be bounded if and only if A is bounded both above and below.

Examples:

N

is bounded below but not bounded.

Z

is neither bounded above or below.

[1, 1] is bounded.

1,

1

1

2 , 3 ,

,

1

n ,

is bounded.

Definition 3:

A sequence {u n } is said to be monotonic increasing if u n u n+1 for each n N.

Similarly, a sequence {u n } is said to be monotonic decreasing if u n+1 u n for each

n N. A sequence which is either monotonic increasing or monotonic decreasing will be

said to be monotonic.

Finally, we say {u n } is strictly monotonic increasing if u n < u n+1 for each n N.

Similarly, we have strictly monotonic decreasing sequences.

Definition 4:

A sequence {u n } is said to converge and to have limit L if and only if for each > 0,

there exists n 0 N such that |u n L| < whenever n > n 0 . If {u n } has limit L, we will

write L = lim

n→∞ u n .

If a sequence {u n } does not converge to any limit L, the sequence is said to diverge.

Page 5-2

5.1.2 Monotone Convergence Theorem

Theorem 1: Monotone Convergence Theorem

(i) If {u n } is a monotonic increasing sequence of real numbers that is bounded above, then

{u n } has a limit. Further, its limit α is the “least upper bound” of {u n }.

(ii) If {u n } is a monotonic decreasing sequence of real numbers that is bounded below,

then {u n } has a limit. Further, its limit β is the “greatest lower bound” of {u n }.

5.1.3 Properties of Convergent Sequences

The three theorems of this section are fundamental tools in analysing the behaviour of sequences.

Theorem 2: Let {u n } and {v n } be sequences, let u =
Theorem 2:
Let {u n } and {v n } be sequences, let u = lim
n→∞ u n and v = lim
n→∞ v n , and let a ∈ R. Then
(i)
n→∞ (u n + v n ) = u + v,
lim
(ii)
n→∞ (u n .v n ) = uv,
lim
(iii)
n→∞ (a.u n ) = au,
lim
(iv)
if for each n ∈ N, we have u n ≤ v n ,
then u = lim
n→∞ u n ≤ lim
n→∞ v n = v.

The following theorem is often called the “squeezing theorem” (or the “pinching theorem”), because it

gives information on the limit of a sequence whose terms are “squeezed” between those of two other

sequences.

Theorem 3:

Suppose that {u n }, {v n } and {w n } are sequences such that u n v n w n for all n N. If

n u n = lim

lim

n w n = L for some L, then lim

n v n exists and also equals L.

Example:

Let u n = sin n . Find

Solution:

We will show lim

We have

n

n u n (if it exists).

lim

n u n exists and equals 0.

for all n N. Also,

n 1 sin n n

1

n ,

lim

n→∞

1

n =

lim

n→∞

1

n = 0.

Therefore, by the Squeezing Theorem, lim n u n exists and equals 0.

Another basic tool for analysing sequences is given in the following theorem, which allows us to use

techniques developed for studying limits of functions (l’Hˆopitals’s rule, for example) to give us information

about limits of sequences.

Page 5-3

Theorem 4:

Let f : R R be a function.

If lim

x f (x) exists, then for n N, lim

n f (n) exists, and lim

x f (x) = lim

n f (n).

Example:

Let u n =

n + 1 , and hence f (x) =

n

2

x + 1 , for x R.

x

2

x f (x) = lim

lim

x→∞

x

+ 1 = 0 (by L’Hˆopital’s rule, or otherwise.)

x

2

Now f (n) = u n =

n + 1 , and so by Theorem 4, lim

n

2

n f (n) = 0.

Example:

In Exercise 2N, Question 4, L’Hˆopital’s rule should have been used to show that

x→∞ lim 1 + x x

1

= e.

It follows immediately from Theorem 4 that the sequence u n : u n = 1 + n n converges with limit

e.

1

Exercise 5A

1. Write down an example of each of the follow- ing:

(a)

a monotonic sequence that does not converge.

(b)

a bounded sequence that does not con- verge.

(c)

strictly monotonic increasing sequence which converges to 4.

(d)

a monotonic increasing sequence of in- tegers that converges.

(a)

2. Determine the values of r for which the

 

sequence {r n }

converges.

(b)

If {r n } converges, find the limit.

3. Determine whether or not the following se- quences converge. If they do, find their lim- its.

(a)

(b)

(c)

2n 1

n

(1) n

n

n 2 2n + 3

n

+ 1

2

ln(n + 1)

(d)

(e)

(f)

(g)

(h)

ln n

n

2

n

n

2

e

2

n

n

e n sin n {1 cos(n + 1)π}

4. Write down an expression for the n th term

for each of the following sequences. Find the limit of the sequences which converge.

(a)

(b)

(c)

(d)

(e)

2

2 , 3 , 3

1

4

4 , 5

,

.

.

.

1,

0,

1 1

1

1 1

, 1 2

, 1

3 ,

ln 2

2

,

2

3

ln 3 , ln 4

3

4

,

.

.

4

.

.

.

.

1,

2

3

4

2 2 1 2 , 3 2 2 2 , 4 2 3 2 ,

1

2 3

.

2 1

, 3 1

, 4

1 ,

2

3

4

.

.

continued next page

Page 5-4

5. We wish to prove that a sequence can have only one limit. Let {u n } be a sequence.

(a)

(b)

(c)

Write down the definition that

L =

lim

n→∞ u n .

Suppose that L 1 = lim

L

Write down the definition that

n u n and

1

= L.

L 1 =

lim

n→∞ u n .

Note that if 1 and 2 are any positive real numbers, there exist n 0 , m 0 N

5.2 INTRODUCTION TO SERIES

5.2.1 Sequences of Partial Sums

for which |L u n | < 1 if n > n 0 , and |L 1 u n | < 2 if n > m 0 .

Rewrite (c) in the particular case when 1 = 2 |L 1 L| and 2 = 2 |L 1 L|.

Use the triangle inequality and (d) to show that if |L 1 L| = 0, then |L 1 L| < |L 1 L|. This is clearly false. Thus, |L 1 L| = 0 and L 1 = L.

Hence, limits of convergent sequences are unique.

(d)

(e)

1

1

Definition 5:

Let {u n } be a sequence. We define a “new” sequence {s n }, called the sequence of partial

sums of {u n }, by the rule that s n =

n

i=1

u i , for each n N.

If we list the terms of {s n }, we see that

s 1 = u 1 ,

s 2 = u 1 + u 2 ,

s 3 = u 1 + u 2 + u 3 ,

s n = u 1 + u 2 + ··· + u n =

n

i=1

u i ,

etc.

The sequence {s n } of partial sums is called a series or an infinite series.

If lim

n s n = S exists, then we have

S =

lim

n→∞

n

i=1

u i ,

and this is usually abbreviated to read

S =

i=1

u i ,

and the limit S is usually called the sum of the series.

Note:

The notation

u n is used both for the sequence of partial sums itself, and for the limit of the sequence

n=1

of partial sums (when it exists).

If lim

n s n = S, we say that

u n is a convergent series.

n=1

If lim

n s n does not exist, then we say that

n=1

u n is a divergent series.

Notation:

Sometimes a summation commences at an index other than n = 1. If it starts with n = 0, for example,

as in

n=0

u n , then the first term corresponds to n = 0, the second to n = 1, etc. (unless we specifically

refer to a “zeroth” term of the series).

Care must be taken in these instances when finding {s n }, the sum to n terms:

s n =

n1

i=0

u i ,

rather than

s n =

n

i=1

u i .

Page 5-5

Example:

Determine if

n=1 2

3 n

converges. If it does, find its sum.

Solution:

At this stage, we have only the definition of a series available as a tool. We will form {s n }, and try to

compute lim

First,

,

n→∞ s n .

s 1 =

2

3 ,

s 2 = 2 3 +

2

3 2

2

3

+ 3 2 + ··· +

2

2

3 n

,

.

.

.

s n =

.

Note that

2 3 s n =

3 2 +

2

2

3 3 + ··· +

3 n +

2

3 n+1

2

.

Therefore,

2

s n 3 s n =

2

3

3 n+1 ,

2

and so

1 3 s n =

2

2

3

2

3 n+1

.

Thus

lim

n s n

=

n→∞ lim 2 3

3 n+1

2

n→∞

=

= 2.

2 3 lim

3 n+1

2

That is,

n=1

2

3 n

converges, with sum 2.

Exercise 5B

1. Find an explicit expression for the n th partial sum of the series

1

2 +

1

1

2

3 +

1

1

3 4

1

+ ··· +

1

n + 1 + ··· .

1

n

Hence find the sum of the series

1

1

1

1

n · (n + 1) + ···.

2. Using a technique similar to that in ques- tion 1, determine whether or not the follow-

1 · 2 + 2 · 3 +

3 · 4 + ··· +

ing series converges:

ln 1 2 + ln 2 3 + ln 4 + · · · + ln n + 1 + ···.

3

n

5.2.2 Some Special Series

(i) Geometric Series

A series of the form

n=0

r n , r R, is called a geometric series (the summation may start at

an index other than 0).

The n th term in the corresponding sequence of partial sums {s n } is given by

s n = 1 + r + r 2 +

+

r n1 .

By the procedure used in the last example, s n can be written as s n = 1 r n

1 r . We conclude that if |r | < 1, then the geometric series is convergent with sum

s =

lim

n→∞ s n =

1

1 r ,

and that if |r| ≥ 1, then the geometric series is divergent.

Page 5-6

(ii) p-Series

A series of the form

n=1

1

p , p R is called a p-series.

n

The p-series obtained by letting p = 1 is called the harmonic series, and has the form

1

n .

n=1

It will be shown using the integral test (Section 5.3.3) that a p-series converges for p > 1, and

diverges for p 1.

5.2.3 The n th Term Test

The definition of convergence is difficult to apply when the partial sums {s n } do not have a simple form.

For this reason, we will develop indirect tests for convergence. The first such test states that a necessary

condition for

n u n = 0.

n=1

u n to converge is that

lim

Theorem 5:

If

n=1

The n th Term Test

u n converges, then lim

n u n = 0.

Consequences of the n th Term Test

Let

n=1

(i)

u n be an infinite series.

If lim

n→∞ u n

= 0, then

n=1

u n diverges.

(ii)

If

n u n = 0, then

lim

n=1

u n may either converge or diverge; that is, in this case, the n th term

test gives no information about the convergence or divergence of

n=1

u n .

5.2.4 Properties of Convergent Series

Theorem 6: ∞ ∞ ∞ Let u n and v n be convergent series, and
Theorem 6:
∞ ∞
Let
u n and
v n be convergent series, and let c ∈ R. Then
c u n
n=1
n=1
n=1
and
(u n + v n ) converge, and
n=1
∞ ∞
(i)
c u n = c
u n ,
and
n=1
n=1
(ii)
(u n + v n ) =
u n +
v n .
n=1
n=1
n=1

Page 5-7

Proof:

(i)

Let

s n =

n

i=1

u i ,

let S n = i=1 n cu i

Then for each n N,

S n

=


=

i=1

= c

= cs n .

cu 1 + cu 2 +

n

cu i

n

i=1

u i

and let

+ cu n

Using the properties listed in section 5.1.3, lim

n S n

=

=

=

s =

lim

n→∞ s n .

lim

n→∞ cs n

c lim

n→∞ s n

cs.

Using a similar argument, we obtain the result that

.

if

n=1

u n diverges, and c

= 0, then

n=1

c u n diverges

Exercise 5C

1.

Determine, giving reasons, whether the fol- lowing series converge or diverge. Find the sum, if it exists.

(a)

(b)

(c)

(d)

n=1

1

5 n

n=1 2 1

3 n1

n=1 3

2

3 n + 2

n=1 4

3

n

1

2

n

2.

(e)

(f)

(g)

n=1

n=1

k=1

n

n

+ 2

1

10n

k 2

k

+ 1

Express the following repeating decimals as rational numbers by summing a geometric se- ries.

(a)

(b)

0.22222

3.013013013

5.3 SERIES OF POSITIVE TERMS

5.3.1 Test 1: Comparison Test

∞ Let u n be a series of positive terms. Further, let n=1 ∞ c
Let
u n be a series of positive terms. Further, let
n=1
c n be a known convergent series of positive terms, and
n=1
d n be a known divergent series of positive terms.
n=1
(i)
If
u n ≤ c n
for each n ≥ n 0 , then
u n converges.
n=1
(ii)
If
d n ≤ u n
for each n ≥ n 0 , then
u n diverges.
n=1

Page 5-8

Proof:

 

(i)

Let

c n be a known convergent series, and let {S n } be the sequence of partial sums for this

 

n=1

 

series.

We note first of all that {S n } is a strictly increasing monotonic sequence which converges.

Thus {S n } is bounded

 
 

 

We now let {s n } be the sequence of partial sums for

u n .

We note that {s n } is a strictly

 

n=1

 

increasing monotonic sequence. Thus, by the Monotone Convergence Theorem, {s n } will converge

provided that it is bounded.

 

For simplicity, we will let n 0 = 1 in the statement of Test 1.

 

Then we have s 1 = u 1

c 1 = S 1 ,

 
 

s 2 = u 1 + u 2

c 1 + c 2 = S 2 ,

 

.

.

.

 

s n = s n1 + u n

S n1 + c n = S n .

 
 

But {S n } bounded implies {s n } bounded.

 

 
 

Thus, {s n } converges, that is,

u n converges.

 
 

n=1

 
 

(ii)

If

u n converges, then by (i),

d n converges.

But we are given that

d n diverges.

 

n=1

n=1

n=1

Thus, we have a contradiction, so

n=1

Example:

Does

n=1

Solution:

STEP 1:

n

+ 1 converge or diverge?

n

2

We apply the n th term test.

lim

n u n

=

lim

n→∞

u n must diverge.

1

n +

1

n

=

0.

Thus, the n th term test gives no information about the convergence of

STEP 2:

Determine the approximate behaviour of

u n =

1

1 n=1

n +

1

n

n .

u n .

n=1

n

n 2 + 1 .

Thus, we would guess that the series “behaves like” the harmonic series, which is

a known divergent series. We now wish to prove that our guess is correct.

STEP 3:

Use Test 1 (the Comparison Test).

1

Since n + n n + 1, we have

1

n + 1 n +

1

1

n

= u n .

But

n=1

1

n + 1 is the harmonic series, less one term, and therefore diverges.

1

If we let d n = n + 1 , then d n u n , and by the Comparison Test,

n=1

u n diverges.

Page 5-9

Remarks:

(1)

(2)

1

If the more obvious inequality n n + n was tried in Step 3, divergence could not be concluded

from the Comparison Test: we would have

u n =

1

n +

1

n

1

n

= d n ,

and the Comparison Test would fail to apply.

1

In Step 3, we could instead have used the inequality n + n n + n = 2n.

5.3.2 Test 2: Comparison Ratio Test

∞ Let u n be a series of positive terms. Further, let n=1 ∞ c
Let
u n be a series of positive terms. Further, let
n=1
c n be a known convergent series of positive terms, and
n=1
d n be a known divergent series of positive terms.
n=1
u
n
(i)
If
lim
= L, then
u n converges, provided that L is
n→∞
c n
n=1
finite.
u
n
(ii)
If
lim
= L > 0, then
u n diverges, provided that L is
n→∞
d
n
n=1
finite.
u
n
(iii)
If lim
= ∞, then
u n diverges.
n→∞
d n
n=1

Proof: (Parts (i) and (ii) when L > 0.)

Let lim

n→∞

u n

c n

= L. ¿From Definition 4, for each > 0, there is n 0 N such that

u

n

c n

L < whenever

n > n 0 .

If we let = L , then there is n 0 N such that

2

Thus, whenever n > n 0 ,

u

n

c

n

L < L

2

whenever n > n 0 .

L + L

2

<

u

c

n

n

<

L + L ,

2

giving

L

2

<

u

c

n

n

<

3L

2 ,

But we know that

c n

n=1

is convergent, which implies that

Therefore, by the Comparison Test,

n=1

u n converges.

and therefore

L

2

c

n

<

n=1

3L

2 c n is convergent.

If we now change the c n ’s to d n ’s and apply the same procedure, we have L d n < u n .

2

Therefore, by the Comparison Test,

u n diverges.

n=1

u n

<

3L

2

c n .

Page 5-10

Example:

Does

n=1

Solution:

n

+ 1 converge or diverge?

n

2

For Step 1 and Step 2, see the example in section 5.3.1.

STEP 3:

Use the Comparison Ratio Test.

Since we have decided that the series u n =

1

n +

1

n

1

we let d n = n in the Comparison Ratio Test.

Now,

lim

n→∞

u n

d

n

=

= 1.

lim

n→∞

n

n +

1

n

Hence, by part (ii) of the Comparison Ratio Test,

“behaves like” the harmonic series,

n=1

u n diverges.

Exercise 5D

1.

Giving reasons, determine whether each of the following series converges or diverges:

4

2

3

5

4 · 6 + ···

(a)

1 · 3 + 2 · 4 + 3 · 5 +

(b)

(c)

(d)

n=1

n=1

n=1

sin 2 n

2

n

e

n

5

n

2n + 1 3n 2 + 1

2.

Let

n=1

u n be a convergent series of positive

terms, and

n=1

v n a divergent series. Prove

or disprove the following statements.

3.

(a)

(b)

(c)

n=1

n=1

n=1

(u n + v n ) is a divergent series.

2

u n is a convergent series.

2

v n is a convergent series.

Prove part (i) of the Comparison Ratio Test if L = 0.

5.3.3 Test 3: The Integral Test

Let f be a decreasing continuous function on [1, ∞). Suppose that f (n) =
Let f be a decreasing continuous function on [1, ∞). Suppose that f (n) = u n is the n th term
of a positive series; that is, we have
u n , where u 1
= f (1), u 2 = f (2),
., u n = f (n).
n=1
Then the series n=1 u n and the integral ∞ f (x) dx either both converge or both diverge.
1

Page 5-11

Example:

Does

n=1

n

+ 1 converge or diverge?

n

2

Solution:

We know from previous examples that this series diverges. In order to apply the integral test, we must

construct a function f (x) to be associated with the series.

STEP 1:

STEP 2:

Let f (x) =

x + 1 . If we let u n =

x

2

n + 1 , then for each n N, f (n) = u n .

n

2

Is f (x) continuous, positive and decreasing on [1, )?

f(x) =

x

2

x + 1

=

f (x) =

x 2 + 1

(x 2 + 1) 2 .

Since x and x 2 + 1 are continous on [1, ), f is continous on [1, ).

If x > 1, then f (x) > 0.

Finally, f (x) < 0 if x > 1.

So f (x) is positive for x [1, ).

So f (x) is decreasing for x [1, ).

Thus, f is continuous, positive and decreasing on [1, ).

STEP 3:

Does f (x) dx converge or diverge?

1

1

x dx x 2 +

1 =

=

=

b→∞ b

lim

1

x dx x 2 + 1

b→∞

lim

1

2 ln(x 2 + 1) b

1

lim

b→∞

1

2 ln(b 2 + 1) 2 ln 2.

1

b ln(b 2 + 1) does not exist. Thus,

1

But lim

x dx

x 2 + 1 diverges.

Hence, by the Integral Test,

n=1

n

2

n + 1 diverges.

Exercise 5E

1. Use the integral test to examine the following series for convergence:

(a)

(b)

(c)

(d)

(e)

1

1

1

· 2 + 2 · 3 + 3 · 4 +

1

1

4 · 5 + ···

1 +

1 1

2 + 3 +

1

4 + ···

1 +

1

1

1

2 3/2 + 3 3/2 +

1

4 3/2 + ···

1 1

1

ln 2 + 3 ln 3 + 4 ln 4 + 5 ln 5 + ···

2

1

1

1 2 + 1 + 2 2 + 1 +

1

3 2 + 1 + ···

2. By considering the following examples, show that the Comparison Ratio Test fails if

Let d n =

1

n and use

n=1

d

n

lim

n→∞

d

n

u

n

= 0.

as a “known divergent series”.

(a)

(b)

1

If u n = n ln n , show that

lim

n→∞

u

n

d

n

By Question 1,

n=1

u n diverges.

1

If u n = n 3/2 , show that

lim

n→∞

u

n

d

n

=

0.

= 0.

By Question 1,

n=1

u n converges.

Parts (a) and (b) show that

lim

n→∞

u

n

d

n

does not imply that

u n diverges.

= 0

n=1

continued next page

Page 5-12

3. Let f be continuous, and non-increasing on [1, ).

If we let F (x) = x f (t) dt, then by the

(a)

i

Fundamental Theorem of Calculus, F is continuous on [i, x] and differentiable on (i, x).

By applying the Mean Value Theorem to F on [i, x], show that there is α (i, x) for which

(b)

(c)

(d)

(e)

(x i)f (α) = F (x).

If we let x = i + 1 in (a), we have

i+1

i

f (x) dx = f (α i ),

where i < α i < i + 1.

Since f is a non-increasing function, we have for each i N,

u i = f(i) f(α i ) f (i + 1) = u i+1 .

Using (b) and (c), we have, for each i

N, u i i+1

f (x) dx u i+1 .

i

Show that

n

i=1

u i

= n+1

1

n

i=1

i+1

i

f (x) dx

f (x) dx

n+1

i=1

u i u 1 .

(f) Show how the LHS of (e) can be used to show that

if

u i converges,

i=1

then f (x) dx converges, and

1

if f (x) dx diverges,

1

then

u i